Deadline-Aware Scheduling Perspectives in Industrial Wireless Networks: A Comparison between IEEE 802.15.4 and Bluetooth. (2nd June 2013) - Collotta, Mario; Pau, Giovanni; Scatà, Gianfranco
In industrial contexts, most of process control applications use wired communication networks. The reliability of wired networks is indisputable and extensively demonstrated by several studies in the literature. However, it is important to consider several disadvantages provided by the use of wired technologies, like high deployment and maintenance costs and low network scalability. Although it is difficult to fully replace wired networks, wireless communication protocols have features which could undeniably affect in positive way the production mechanisms in factories. The wireless networks (WNs) are effectively used to detect and exchange information. The main communication protocols, currently available for WNs, however, do not support real-time periodic traffic flows which, as known, mainly characterize industrial networks. In this paper, we will analyze a real-time scheduling algorithm for both periodic and aperiodic traffic management, applied to networks based on IEEE 802.15.4 and Bluetooth, respectively. The main purpose of this research is to reduce, as much as possible, the packet loss on the channel, increasing at the same time the reliability of the wireless technology. Furthermore, the comparison between IEEE 802.15.4 and Bluetooth will allow to identify the more suitable communication protocol for industrial process control systems.